ANALISIS RENCANA PELAKSANAAN PEMBELAJARAN (RPP) MAHASISWA CALON GURU BIOLOGI - Rizkia Suciati; Yuni Astuti (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2016)
Abstract The study aimed to find out the quality of prospective biology teacher lesson plan based on component standard of lesson plan (BSNP). The sample was the VI semester biology education student choosen by stratified random sampling. The data was collected through 10 component of checklist. The result shows: 1) the form of lesson plan made is valued 10 (18,18%), 8 (27,27%), and 5 (3,03%); 2) the learning indicator development, 27,27% are appropriate with KI/KD; 3) in cognitive skill indicator development, C2 is the highest (55,12%), and C6 is the lowest (0,79%); 4) the clarity in detailing the scientific based teaching-learning situation, 18,18% are very detail, systematic, and relevant to indicators 5) the conformity in choosing and using the learning method reaches 39,39%, and 30,30% students can connect the learning media and the learning method, KI/KD, and indicator; 6) 18,18% students used the various learning source; 7) 33,33% material selection is approriate with the indicator; 8) 48,48% students can detail the time allocation in teaching-learning scenario; 9) in the evaluation aimed, 48,08% refers to science concept (science product), 15,38% (science process), 36,54% scientific attitude; 10) in the learning evaluation technic, 34,67% (essay), 26,67% (observation), and 24% (performance assesment). Overall, the ability of prospective biology teachers in compossing standard lesson plan are in quite good category, but the conformity of indicators with KI/KD, method chose, media, the learning source, and the proper materials are need to be improved. The selection of learning technic evaluation are various. Keywords: lesson plan analysis; prospective teacher Abstrak Penelitian bertujuan untuk mengetahui kualitas RPP mahasiswa calon guru biologi sesuai standar komponen RPP (BSNP). Sampel merupakan mahasiswa biologi semester VI, stratified random sampling. Pengumpulan data melalui checklist dengan 10 komponen. Diperoleh hasil: 1) Format RPP yang dibuat, nilai 10 (18,18%), 8 (27,27%), dan 5 (3,03%), 2) Pengembangan indikator pembelajaran, 27,27% sesuai dengan KI/KD, 3) Pengembangan indikator kemampuan kognitif, tertinggi C2 (55,12%), dan terendah C6 (0,79%), 4) Kejelasan merinci KBM berbasis pendekatan ilmiah, 18.18% sangat rinci, sistematis, relevan dengan indikator; 5) Kesesuaian memilih dan menggunakan metode belajar untuk pencapaian indikator 39,39% dan 30,30% mampu merelevansikan antara media/alat belajar dengan metode belajar serta KI/KD dan indikator, 6) 18,18% menggunakan sumber belajar bervariasi, 7) Pemilihan materi pembelajaran sesuai indikator (33,33%), 8) Kemampuan merinci alokasi waktu dalam skenario KBM (48,48%), 9) Sasaran penilaian yang dituju, 48.08% mengacu pada konsep sains (produk sains), 15.38% (proses sains), dan 36,54% (sikap ilmiah), 10) Pemilihan teknik evaluasi pembelajaran, 34,67% (tes uraian), 26,67% (teknik observasi), dan 24% (asesmen kinerja). Secara keseluruhan, kemampuan mahasiswa calon guru Biologi dalam menyusun RPP yang memenuhi standar dalam kategori cukup baik, namun kesesuaian indikator dengan KI/KD, pemilihan metode, media, sumber belajar, dan kesesuaian materi masih perlu diperbaiki. Pemilihan teknik evaluasi pembelajaran pun beragam. Kata Kunci: analisis RPP; calon guru Permalink/DOI: http://dx.doi.org/10.15408/es.v8i2.4059